2017
DOI: 10.3892/mmr.2017.6790
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation attenuates cardiac hypertrophy in spontaneously hypertensive rats via regulation of autophagy

Abstract: It has been suggested that renal denervation (RD) may attenuate left ventricular (LV) hypertrophy. However, the role that autophagy serves in this process is currently unclear. In the present study, utilizing a model of hypertension-induced cardiac hypertrophy in spontaneous hypertensive rats, it was demonstrated that RD was significantly associated with a reduction in LV hypertrophy. Furthermore, a decrease in the myocardial mRNA of hypertrophy-associated genes was demonstrated in RD rats compared with sham c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The different effects of RDN on autophagy in various disease models have been previously studied. Huang et al have reported that RDN plays a cardioprotective role via reduction of autophagic responses in spontaneously hypertensive rats, while Liu et al have shown that RDN ameliorates cardiac dysfunction by enhancing autophagy in rats with diabetes. In the present study, we found that RDN indeed regulated autophagic flux after pressure overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different effects of RDN on autophagy in various disease models have been previously studied. Huang et al have reported that RDN plays a cardioprotective role via reduction of autophagic responses in spontaneously hypertensive rats, while Liu et al have shown that RDN ameliorates cardiac dysfunction by enhancing autophagy in rats with diabetes. In the present study, we found that RDN indeed regulated autophagic flux after pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…Our group also has found that RDN promotes cardiac angiogenesis in a rat model of transverse aortic constriction (TAC)‐induced cardiac hypertrophy . A more recent study performed on spontaneously hypertensive rats revealed a potential association between cardiac protection of RDN and autophagy . However, whether and how RDN affects autophagic activity in cardiac remodelling and heart failure induced by TAC is not known.…”
Section: Introductionmentioning
confidence: 98%